Reliability and maintenance modeling for competing failures with intermission considered. (October 2019) - Liu, Jingyi; Zhang, Yugang; Song, Bifeng
There are many industrial systems experiencing multiple dependent competing failure processes, in detail degradation failure (soft failure) and catastrophic failure (hard failure). Earlier research studied failure behaviors and system reliability during operational period, but did not consider the intermission period. Some industrial systems are not always operating continuously while with intermissions or rest period. The degradation and random shock processes are different between operating period and intermissions, which caused it more challenging and complicated to establish reliability model. In this article, a new reliability model for multiple dependent competing failure processes is developed with intermission considered. The system reliability can be analyzed based on the proposed model more practically. Besides, a preventive replacement maintenance policy is studied by minimizing the average long-run maintenance cost with intermission periods considered. Finally, the availability and general applicability of presented model are demonstrated by a case in different parameter settings.